Improvement of Student Learning Outcomes through the Development of a Flat-based Building Material Teaching Module Based on RME Approach in Class VII MTs Integrated Langsa City - Hernita Hernita (Randwick International of Education and Linguistics Science Journal, 2023)
This study aims to describe: 1) The validity, practicality and effectiveness of teaching materials on flat shapes based on the developed Realistic Mathematics Education (RME) approach. 2) Improving student learning outcomes on flat material. This research is a development research using the ADDIE model which is carried out in class VII Integrated MTS Langsa City. The research results obtained are: 1) The teaching materials developed have been categorized as Valid, Practical and Effective. 2) Based on the normalized gain index, it is found that there is an increase in student learning outcomes after using the developed teaching materials. Based on classical student completeness, the percentage of student completeness in the tests carried out was that students completed 29.3% of students completed the pre-test and 86% of students completed the post-test. Thus, the development of teaching materials for flat shape materials based on the Realistic Mathematical Education (RME) approach developed can improve student learning outcomes for class VII MTS Integrated Langsa City